Teljesítményértékelés a gyakorlatban - Juhász, Csilla (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
Performance management is one of the most important fields of management. For the evaluation of it, I have worked out a questionnary. In this questionnary I studied the importancy and method of performance evaluation. I hope my results may contribute to the reveal of practise of performance evaluation. Based on my examinations I have found that feedback for the employees was that factor, which was considered most important by interviewees at the study of performance appraisal objectives. The performance appraisal system is mainly influenced by corporate values and management. Of the others, the evaluation of tasks performed was highlighted as the most positively appraised factor. The person of the evaluator coincides with ruler manager of the traditional aspect, who may be a direct manager of the workplace or a superior manager. Examinations show that organizations mainly apply traditional systems and think by the traditional aspect.